Anti-VEGF treatment patterns and associated health care costs in Switzerland: findings using real-world claims data - Reich O; Bachmann LM; Faes L; Böhni SC; Bittner M; Howell JP; Thiel MA; Rapold R; Schmid MK (Dove Medical Press, 2015)
Oliver Reich,1 Lucas M Bachmann,2 Livia Faes,3 Sophie C Böhni,3 Mario Bittner,3 Jeremy P Howell,3 Michael A Thiel,3 Roland Rapold,1 Martin K Schmid3 1Department of Health Sciences, Helsana Group, Dübendorf, 2Medignition Inc, Research Consultants, Zurich, 3Eye Clinic, Cantonal Hospital of Lucerne, Lucerne, Switzerland Background: Little is known about the patterns of actual health care delivery of anti-vascular endothelial growth factor (VEGF) treatment in patients with age-related macular degeneration, diabetic retinopathy, and retinal vein occlusion in Switzerland. The purpose of this study was to describe these treatment patterns, specifically comparing the numbers of anti-VEGF injections and associated expenditures between patients treated with ranibizumab and those treated with aflibercept in Switzerland using claims data. Methods: We identified our study patients retrospectively using the Helsana claims database, which includes data on approximately 1.2 million subjects with basic health insurance. Patients qualified for inclusion if ranibizumab or aflibercept had been initiated between December 1, 2012 (when aflibercept was approved by the Federal Office of Public Health) and November 30, 2013. Within this set, patients with at least 12 months of continuous insurance enrolment in the previous year were considered. In univariate analyses, we examined the distribution of demographic data and patient characteristics between those receiving ranibizumab and those receiving aflibercept. Numbers of injections and associated health care expenditures observed during the 6-month follow-up period after incident treatment were the two outcomes considered. In multivariate regression analyses, controlling for possible confounding factors, we compared differences in these two outcomes between patients treated with ranibizumab and those treated with aflibercept. Results: Of 3,260 patients who were on anti-VEGF treatment for an ophthalmological indication between December 1, 2012 and November 30, 2013, 1,150 qualified for inclusion. Age, geographic region, and number of physician visits in the previous year were significant factors in the number of injections given during the 6-month follow-up period. Frequency of injections and associated health care expenditures were similar between the groups when correcting for differences in patient characteristics. Conclusion: Contrary to the recommendations regarding frequency of injections and the results of clinical studies, aflibercept and ranibizumab are used in a similar fashion in Switzerland, resulting in similar total health care expenditures for both these anti-VEGF agents. Keywords: ranibizumab, aflibercept, health care costs, Switzerland